Važnost promocije u sveučilišnome sportu na fakultetskoj razini - analiza slučaja : Fakultet za odgojne i obrazovne znanosti u Osijeku 2014.-2020. = The importance of the promotion of university sport on the faculty level - case analysis : Faculty of Education Osijek 2014 to 2020 - Galić, Tvrtko (Array, 2020)
The ways of informing students about the activities which are organized on a faculty or university level daily present an increasing challenge. The very aim of this work is to analyze and compare ways of informing students of the Faculty of Education about the sport activities on the faculty and university level. The way of informing students about the activities will be compared with the ways of informing about general sport activities in order to identify possible deviation from two different types of activities. Promotion being one of the marketing elements, so is the appliance of adequate promotion tools very important in all social processes. Numerous examples, especially in sport, proved that the activities of the sport participants will not be successful without the adequate use of promotion. University sport in developed countries surely occupies an important place in the academic community; from that point of view it is very important to determine the way of managing the university sport. The university sport in the Republic of Croatia is becoming more significant element of students' activities every day, and the promotion contributes to that. Apart from comparing the ways of informing about sport and regular activities, this paper will provide the time comparison of the mentioned researches between 2014 and 2020. The comparison of the same data with the time lag will provide the best picture of the changes in the ways of informing in a 6-year-period. The obtained results have shown that even after six years, students continue to prefer certain communication channels, i.e. they remain primary.